Structural insights into muscle organisation by electron cryo-tomography - Wang, Zhexin (Technische Universität Dortmund, 2022)
Movement is the essence of life in the animal realm. Skeletal muscle is an essential tissue specialised for movement. Muscle cells are multi-nucleated cells containing bundles of myofibrils, which are segmented into the smallest contractile units, named sarcomeres. While sarcomeres are known to contain thin (actin) and thick (myosin) filaments, the detailed architecture, especially the high-resolution and 3-dimensional (3D) information, remains obscure. In this thesis, I obtained the first high-resolution 3D pictures of the sarcomere using cryo-focused ion beam milling (cryo-FIB-milling) and electron cryo-tomography (cryo-ET). The sarcomere organisation highlights a molecular plasticity which ensures efficient muscle contraction in different environments. Furthermore, from these native 3D images, I determined the first structures of the ruler protein, nebulin, to a resolution of 4.5 Å, which establishes the molecular basis for its functions in thin filament stabilisation, length control and myosin-binding regulation. The in situ structures also revealed a double-head conformation of myosin that reveals inherent variability to increases myosin’s capability for binding to the thin filaments. Collectively, my thesis research provides unique insights into muscle structures that allow improved dynamic modelling of muscle contraction and muscle diseases. This research also establishes a new cryo-FIB-ET approach for structurally characterising muscle components in different types of muscles and diseased states.
Keywords: Muscle; Sarcomere; Actin; Myosin; Nebulin; Cryo-ET; 570; 540; Muskel; Sarkomer; Actin; Myosin